It's in the data: Improved market power mitigation in electricity markets - Jacqueline Adelowo; Moritz Bohland (EconPol Forum, 2023)
Some electricity markets use automated mitigation procedures against market power abuse. This requires marginal cost estimates, which have to be derived from observed auction bids. Current stimation procedures can be improved by using available auction data more systematically. Our redesign delivers more precise estimates and reduces the risk of strategic manipulation by firms. Precise mitigation allows for welfare gains and transfers to buyers in a simulation
Keywords: 330